The implementation of quadruple helix model and competitive advantage to the growth of creative industries in Malang District - Muljaningsih , Sri (Future Science, 2020)
The purpose of this research is a concept based on the Quadruple Helix model and Competitive Advantage towards the development of the creative industry in Malang Regency. The variables used in this study include Variable freedom consisting of the variable Competitive Advantage and Quadruple Helix variables, on the other hand, the dependent variable is the development of the Creative Industry in Malang Regency. The population in this research is all Creative Industries in Malang Regency. The illustration of this research is the leaders and managers who represent the Creative Industry in Malang Regency which has 30 respondents. The method of analyzing information in this research uses Partial Least Square with the Smart PLS M3 application. PLS is a procedure for creating a predictable building model when there are many aspects. Based on research results, it can be shown that competitive advantage can provide significant donations to the development of the creative industry. Quadruple Helix cannot distribute a significant donation for the development of the Creative Industry.